2019
DOI: 10.1093/infdis/jiz115
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum Clearance Is Pitting-Dependent With Artemisinin-Based Drugs but Pitting-Independent With Atovaquone-Proguanil or Mefloquine

Abstract: Pitting, the removal of dead parasites from their host erythrocyte, has been studied in patients with severe malaria treated parenterally with quinine or artesunate, and was recently shown to contribute to delayed hemolysis, a frequent adverse event of artesunate. We quantified pitting in 81 travelers treated with oral antimalarial therapy. Pitting rate was high (55.8%) with artemisinin-based combinations, but <10% with the nonartemisinin drugs quinine, mefloquine, and atovaquone-proguanil. This may, in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…After pitting, once-infected red cells still containing HRP2 (exported to the erythrocyte before pitting, see earlier) return to the circulation [76,77], where they persist for several weeks, corresponding to the period of persisting mRDT positivity. This explains a previously reported finding of artemisinin-based treatment being associated with rapid parasite clearance but slower HRP2 clearance than the antifols [78], which, similar to other slower acting drugs [79], allow parasites to mature and sequester leading to more rapid HRP2 clearance [78] (Figure 2). PCR amplifies at least two single copy genes from the same sample (not ribosomal genes, which are multicopy)…”
Section: Other Sources Of Inaccuracysupporting
confidence: 64%
“…After pitting, once-infected red cells still containing HRP2 (exported to the erythrocyte before pitting, see earlier) return to the circulation [76,77], where they persist for several weeks, corresponding to the period of persisting mRDT positivity. This explains a previously reported finding of artemisinin-based treatment being associated with rapid parasite clearance but slower HRP2 clearance than the antifols [78], which, similar to other slower acting drugs [79], allow parasites to mature and sequester leading to more rapid HRP2 clearance [78] (Figure 2). PCR amplifies at least two single copy genes from the same sample (not ribosomal genes, which are multicopy)…”
Section: Other Sources Of Inaccuracysupporting
confidence: 64%
“…FIKK4.2 localizes to a compartment of the infected erythrocyte distinct from the Maurer's clefts or J-dots, and disruption of the gene encoding FIKK4.2 leads to dramatically altered mechanical properties and cytoadherence of infected erythrocytes ( Kats et al, 2014 ). Specifically, erythrocytes infected with FIKK4.2 knockout parasites were less rigid and less adhesive than erythrocytes harboring parasites with functional FIKK4.2 ( Kats et al, 2014 ), a phenotype also observed in cells infected with artemisinin-resistant parasites ( Ndour et al, 2015 ; Wojnarski et al, 2019 ). Further studies would be required to determine whether mutations in FIKK4.2 contribute to changes in deformability observed in artemisinin resistant parasites.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have indicated that in populations with less antimalarial immunity, “pitting” (i.e., splenic removal of parasites from infected erythrocytes) is a major mechanism for rapid parasite clearance following treatment with artemisinin derivatives ( Ndour et al, 2015 ; Wojnarski et al, 2019 ). However, erythrocytes infected by artemisinin resistant parasites have been shown to have increased deformability and reduced splenic pitting, allowing them to remain in circulation ( Wojnarski et al, 2019 ). One unexplored hypothesis is that exported proteins could contribute to the altered deformability and reduced splenic clearance of artemisinin-resistant parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Pitting appears to be an important contributor to clearance in infants, who are expected to have low anti-parasite humoral immunity; however in older children, immunity correlates with an even faster parasite clearance, likely through immune-mediated phagocytosis, and possibly through splenic retention without pitting [50]. Pitting is marked in patients treated with intravenous artesunate or oral artemisinin derivatives, and much lower after treatment with quinine, mefloquine or atovaquone-proguanil [51].…”
Section: Contribution Of Pitting To Parasite Clearancementioning
confidence: 99%